2021
DOI: 10.3389/fpsyg.2021.738954
|View full text |Cite
|
Sign up to set email alerts
|

Learning Through Digital Stories for Safe School Environment

Abstract: This study aimed to evaluate the impact of digital stories in the learning-based themes of safe schools and to examine the perceptions of special educational needs in safe school environments. Training were carried out with informative videos created through the Distance Education and Information Technology Center (UZEBIM) for principals and teachers-in-charge, and the effectiveness of this process was evaluated through reflective opinion forms. In addition to this, an evaluation form was presented to the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…In recent years there have been many attempts to create a general understanding of what makes the school environment safe, especially in the psychological and educational field [e.g., 54 , [55] , [56] , [57] , [58] , [59] ]. Usually, researchers emphasise the importance of a positive school climate when they address safety issues in schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years there have been many attempts to create a general understanding of what makes the school environment safe, especially in the psychological and educational field [e.g., 54 , [55] , [56] , [57] , [58] , [59] ]. Usually, researchers emphasise the importance of a positive school climate when they address safety issues in schools.…”
Section: Discussionmentioning
confidence: 99%
“…This can also be seen as a discrimination and safety issue in schools. Akdag et al found in their study that special school institutions do not have a sufficient level of school safety and the technological infrastructure is not satisfactory [ 55 ]. Savolainen and Airo have similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel to this, there have been further studies on the use of technology in teaching Turkish as a foreign language as well as in global foreign language education. In this context, integration of technology with language learning-teaching (Birinci, 2020;Repetto et al, 2021;Van Lieshout and Cardoso, 2022), the use of web 2.0 tools, social media, blogs and extracurricular learning environments in language teaching (Bozavli, 2017;Taylan, 2018;Ustabulut and Keskin, 2020;Inal and Arslanbaş, 2021;Sarigül, 2021), digital stories (Akdag and Altinay, 2021;Çokyaman and Çelebi, 2021;Kazazoglu and Bilir, 2021), e-portfolios (Erice and Ertaş, 2011), virtual classrooms (Parmaxi, 2020), and robot teachers (Edwards and Cheok, 2018) have been addressed in the literature. Nevertheless, the results of these studies on the competencies of both teachers and students regarding the use of technology in the language learning-teaching process are contradictory.…”
Section: Learning Technologies In Foreign Language Educationmentioning
confidence: 99%
“…Video dipilih karena sesuai dengan cara belajar anak yang memerlukan visual dan audio karena anak belum bisa berpikir secara abstrak. Penelitian lainnya menunjukkan bahwa dongeng menjadi salah satu media yang baik dalam sebuah program intervensi untuk mempersiapkan anak kembali ke sekolah yang menggambarkan bahwa lingkungan sekolah telah aman (Akdag & Altinay, 2021;Kadiasti & Mukaromah, 2021). Dengan demikian, adanya video animasi ini dapat dijadikan sebagai media dongeng untuk meningkatkan pengetahuan anak tentang Covid 19 dan mempersiapkan anak untuk kembali ke sekolah sehingga anak dapat mengingat, dan mencontoh perilaku yang dapat membiasakan anak melakuan perilaku tersebut serta menjaga kesehatan, sehingga dimasa anak dapat mencegah dan menjaga diri dari Covid 19 selama belajar di sekolah.…”
Section: Pembahasanunclassified